The library of lost dollhouses : a novel - Hooper, Elise (William Morrow, an imprint of HarperCollinsPublishers, 2025)
"Tildy Barrows, Head Curator of a beautiful archival library in San Francisco, is meticulously dedicated to the century's worth of inventory housed in her beloved Beaux Art building. She loves the calm and order in the shelves of books and walls of art. But Tildy's life takes an unexpected turn when she, first, learns the library is on the verge of bankruptcy and, second, discovers two exquisite never-before-seen dollhouses. After finding clues hidden within these remarkable miniatures, Tildy sets out to decipher the secret history of the dollhouses, aiming to salvage her cherished library in the process. Her journey introduces her to a world of ambitious and gifted women in Belle Époque Paris, a group of scarred World War I veterans in the English countryside, and Walt Disney's bustling Burbank studio in the 1950s. As Tildy unravels the mystery, she finds not only inspiring, hidden history, but also a future for herself -- and an astonishing familial revelation"--